Assessing the mental health of slum dwellers: an ordinal logistic approach - Nasim Bin Jinnah Hijol; Nahid Salma; Indrani Sarker (BMC, 2024)
Abstract Background Stress, depression and anxiety are prevalent mental health concerns that are getting worse every day in the context of rapidly expanding megacities, where a rising number of people live in slums. The purpose of this study is to evaluate the state of mental health and related variables underlying mental health issues among the impoverished population. Methodology A total of 384 slum residents from the Khulna division responded to our questionnaire, which included the DASS-21 and other pertinent questions. Using ordinal logistic regression, the significant factors were extracted. Results The Cronbach's reliability coefficient for the DASS-21 scale lies between 0.79 and 0.89 which indicates the high reliability of the DASS-21 scales. According to the findings, roughly 72.7%, 84.1%, and 69% of participants slum dwellers experienced anxiety, depression, and anxiety problems respectively. The result of ordinal logistic regression shows, slum dwellers of female gender (B = 0.669*, 95% CI 0.141, 1.197), married (B = 1.506*, 95% CI 0.119, 2.893), having only one earning member in the family (B = 1.224*, 95% CI 0.526, 1.922), day laborers (B = 2.294*, 95% CI 1.115, 3.473), not being able to educate children due to financial problem (B = 0.558*, 95% CI 0.183, 0.932) were more likely to report high levels of anxiety, depression, and stress. Conclusion The study finds that a significant portion of people who live in slums struggle with mental health issues. It also points to the need for further support, intervention, and study on Khulna's slum inhabitants who are experiencing mental health issues. The authors anticipate that the results will spur policymakers and government representatives to enhance financing for slum dwellers and employ psychological intervention strategies, both of which will aid in achieving the Sustainable Development Goal.